2003
DOI: 10.1177/0887403403254492
|View full text |Cite
|
Sign up to set email alerts
|

Race and Misdemeanor Sentencing

Abstract: This research examines the validity of an integrative theoretical approach that consists of the "liberation hypothesis" and the "focal concerns" perspective to assess the extent racial discrimination is likely to occur in misdemeanor decision making involving less serious cases. We examined decisions involving the prioritizing of cases, the granting of a continuance, conviction, and incarceration in a large county court in a southeastern state. The results fail to provide support for the belief that the likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 49 publications
1
25
0
2
Order By: Relevance
“…Studies have generally concluded that Hispanic defendants received harsher sentences than either Caucasian or Black defendants (Demuth & Steffensmeier, 2004;Steffensmeier & Demuth, 2001), were less likely to receive departures (Hartley, Maddan, & Spohn, 2007), and received smaller sentence reductions in downward departures (Steffensmeier & Demuth, 2000, see also Albonetti, 1997). Other research reported that minority status is a more important factor in serious cases than non-serious cases (Leiber & Blowers, 2003). Finally, the importance of the type of case (guideline versus mandatory minimum), the type of drug (crack versus powder cocaine) (Hartley et al, 2007), and the district in which the case was sentenced (Hartley, 2008;Johnson, Ulmer, & Kramer, 2008;Spohn, 2005) were all factors affecting sentencing decisions for minorities.…”
Section: Building Knowledgementioning
confidence: 91%
“…Studies have generally concluded that Hispanic defendants received harsher sentences than either Caucasian or Black defendants (Demuth & Steffensmeier, 2004;Steffensmeier & Demuth, 2001), were less likely to receive departures (Hartley, Maddan, & Spohn, 2007), and received smaller sentence reductions in downward departures (Steffensmeier & Demuth, 2000, see also Albonetti, 1997). Other research reported that minority status is a more important factor in serious cases than non-serious cases (Leiber & Blowers, 2003). Finally, the importance of the type of case (guideline versus mandatory minimum), the type of drug (crack versus powder cocaine) (Hartley et al, 2007), and the district in which the case was sentenced (Hartley, 2008;Johnson, Ulmer, & Kramer, 2008;Spohn, 2005) were all factors affecting sentencing decisions for minorities.…”
Section: Building Knowledgementioning
confidence: 91%
“…However, variables from all three characteristic types (victim, offender, and offense) remained in the analysis, showing that sending a convicted offender to prison and the length of the prison sentence is a complex process where information on a variety of characteristics are taken into account. It is encouraging to note that neither offender nor victim ethnicity was related to sentencing of convicted child sex offenders; while ethnicity might play a role earlier in the criminal justice process (Leiber & Blowers, 2003), in the cases analyzed it did not appear to play a part postconviction. However, it should be noted that the population of this state is very homogeneous (White), with the only large minority group being Hispanic.…”
Section: Discussionmentioning
confidence: 99%
“…Spohn and Cederblom (1991) examined the sentences imposed on defendants convicted of felonies and found that the defendant's race had a direct effect on the incarceration decision in less serious cases only. Leiber and Blowers (2003) explored the extent to which racial discrimination was likely to occur in misdemeanor cases involving less serious cases. They found that race influenced misdemeanor decision making both directly and indirectly.…”
Section: Theoretical Perspectivementioning
confidence: 99%